2010 International Conference on Microwave and Millimeter Wave Technology 2010
DOI: 10.1109/icmmt.2010.5524947
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of a novel UWB antenna array

Abstract: A novel 1 4 planar UWB antenna array is proposed. The utilized single element is a compact planar circular slot micro-strip antenna. The feeding network is 1 to 4 Wilkinson power divider. The bandwidth of the antenna array is from 3.1GHz to 12.4GHz and the radiation pattern is bidirectional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In Reference , four elements UWB antenna array with a wideband Wilkinson power divider feeding system is presented. In Reference , a four elements UWB antenna array is presented.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference , four elements UWB antenna array with a wideband Wilkinson power divider feeding system is presented. In Reference , a four elements UWB antenna array is presented.…”
Section: Introductionmentioning
confidence: 99%
“…When designing antenna array, problems associated with the integration of antenna element and feeding network such as mutual coupling among antenna elements must be considered carefully [9]. Several studies about UWB planar antenna have been done.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Wang (2008) in their recent study have integrated the feed network into an array of antennas, but have not shown the experimental results of their work. In (Chen and Wang, 2010;Huang and Xu, 2010), the authors have presented experimental results of their proposed UWB arrays, but did not investigate the method to suppress the side lobe level of the arrays. One of the important issues in designing arrays is the mutual coupling between elements.…”
Section: Introductionmentioning
confidence: 99%